2008
DOI: 10.2746/042516408x251921
|View full text |Cite
|
Sign up to set email alerts
|

Determination of MMP‐2 and ‐9 activities in synovial fluid of horses with osteoarthritic and arthritic joint diseases using gelatin zymography and immunocapture activity assays

Abstract: These findings encourage the potential use of MMP-2 and -9 as additional aids to clinical investigation. Further work is required to validate the clinical significance of MMP activities in the progress of different joint diseases in horses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 23 publications
4
17
0
Order By: Relevance
“…These observations suggest enhanced expression and activation of MMP-9 in septic knee arthritis compared with the aseptic, which is consistent with previous studies [2,4,7,20]. These observations suggest enhanced expression and activation of MMP-9 in septic knee arthritis compared with the aseptic, which is consistent with previous studies [2,4,7,20].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These observations suggest enhanced expression and activation of MMP-9 in septic knee arthritis compared with the aseptic, which is consistent with previous studies [2,4,7,20]. These observations suggest enhanced expression and activation of MMP-9 in septic knee arthritis compared with the aseptic, which is consistent with previous studies [2,4,7,20].…”
Section: Discussionsupporting
confidence: 92%
“…Arican et al found increased concentrations of MMP-9 activity in the synovial fluid of cows with septic arthritis in comparison with fluids from normal joints, using gelatin zymography and ELISA [2]. Two more animal studies confirmed the above data in horses and calves [7,9]. Two more animal studies confirmed the above data in horses and calves [7,9].…”
Section: Discussionmentioning
confidence: 79%
“…Minocycline was tested at ranges from 0 to 4000 μg/mL (8.1 × 10 −6 M). Exhibiting close homology to equine MMPs, human‐recombinant MMP‐2 and MMP‐9 (rhMMP‐2 and ‐9, Calbiotech, Spring Valley, CA) was each used at 10 μg/mL . A stock solution of pure minocycline (Sigma‐Aldrich Fine Chemicals, St Louis, MO) was prepared in PBS.…”
Section: Methodsmentioning
confidence: 68%
“…It was decreased when the affected horses were successfully treated [32]. It has been reported that the potent stimulators of cartilage degradation such as IL-1 β and TNF- α upregulated MMP-2 gene expression by selectively inducing mitogen-activated protein kinase (MAPK) signaling pathway via MKK3/6-p38, leading to phosphorylation of the activating transcription factor 2 (AP-2) which consequently mediated transcriptional processing of MMP-2 gene [33, 34].…”
Section: Discussionmentioning
confidence: 99%